Serological investigation of Leishmania infantum, Dirofilaria immitis and Angiostrongylus vasorum in dogs from southern Portugal - Maia, Carla (2015)
Background: Leishmaniosis, dirofilariosis and angiostrongylosis are parasitic diseases of established importance in dogs worldwide. The aim of the present report was to determine all together levels of infection with or exposure to Leishmania infantum, Dirofilaria immitis and Angiostrongylus vasorum in dogs from the Algarve region, in southern Portugal. Findings: Serum samples were obtained from a total of 170 apparently healthy dogs. Antibodies to L. infantum were detected by the direct agglutination test; and antigens of D. immitis and of A. vasorum by an enzyme-linked immunosorbent assay and an immunochromatography test, respectively. Antibodies to L. infantum were found in 18.2% (31/170) of dogs, while D. immitis antigen was detected in 9.4% (16/170). None of 120 dogs tested out of the 170 under investigation had evidence of infection with A. vasorum. D. immitis infection was more prevalent in dogs aged 84-204 months than in those younger than 12 months. Three dogs were positive to both L. infantum and D. immitis. Conclusions: Dogs living in southern Portugal are at risk of leishmaniosis and dirofilariosis. This scenario should make the veterinary community, local dog owners and also tourists from non-endemic countries coming on vacation with their pets aware of the need of effective prophylactic measures, in order to protect animals and public health.